Mango (Mangifera indica L.) leaves waste/polyvinyl acetate biocomposite for building materials application - Masturi,; Alighiri, Dante; Widya Nurul Jannah,; Maulana, Riful Mazid; Amri, Ulul; Susilawati,; Sunarno, (Penerbit Universiti Kebangsaan Malaysia, 2020)
A leaves waste biocomposite was produced via a simple mixing and hot-pressing process. Using mango (Mangifera indica L.) leaves waste as a filler and polyvinyl acetate (PVAc) as a binder, the biocomposite was synthesized at pressure and temperature of 3 metric tons and 40°C, respectively, for 20 minutes. The weight fraction of leaves waste varied obtaining a composite having maximum compressive strength, i.e., 37.82 MPa for leaves waste fraction of 0.62 (w/w). This strength is comparable to several stones such as sandstone stone, limestone, clay brick, aspen wood, and pinewood usually used as building materials. Therefore, the biocomposite is acceptable for building materials application.